MODEL FOR ESTIMATING THE EFFICIENCY OF VIDEO DATA ENCODING IN SPECTRAL-PARAMETRIC SPACE - Elіseev Evgenіy (Science-based technologies, 2025)
From the point of view of providing high-quality information services, it is important to ensure the required quality of standard information: timeliness of information transmission, reliability of information, completeness of content, continuous provision of information according to the needs of users. For this, complex actions are used, including technological, mathematical and hardware and software. Appropriate exchange protocols and information presentation technologies are being developed. At the same time, the development of existing and the emergence of new information services leads to the formation of new requirements for the mathematical and technological basis for their implementation. This also includes the need for further development of technologies and methods of presenting information. Currently, one of the most powerful standardized implementations is the JPEG format. Modern methods use more powerful improvements to the listed mechanisms. This allows you to achieve better results according to the system "loss level - compression level". However, most of the solutions are aimed at improving the quality of visual assessment using noise filters and appropriate machine learning methods. It is these actions that are performed on the receiving side. Hence, there is a need to improve redundancy reduction techniques to increase the level of video data compression. One of the areas that has the potential to further reduce redundancy without additional distortion is the technology for representing video data in spectral-parametric space. For this technology, there are opportunities for additional consideration: the level of information content of the transformant sequence; the presence of dependencies in data sets to reduce statistical and structural mean-transformant redundancy. At the same time, there is no model for evaluating their effectiveness taking into account various factors and parameters of the compression method. Otherwise, it allows to increase the level of validity of estimates obtained theoretically and experimentally. Therefore, the purpose of the article is to develop a model for evaluating the effectiveness of video data encoding in spectral-parametric space. A model has been developed for estimating the number of bits per common code of the clustered sequence of transformants in the SPPT based on their compression by the developed method. In the process of calculation, the peculiarities of the construction of individual components of the service and information parts of the general codegram are taken into account.